Advances in Advertising Research IX Power to Consumers (European Advertising Academy,, 2018)
This book addresses challenges and opportunities in research and management related to new advertising and consumer practices in a converging media society. It specifically relates to the increasing power of consumers in the (digital) marketing process and discusses the challenges this may bring to advertisers. Advances in Advertising Research are published by the European Advertising Academy (EAA). This volume is a selective collection of research presented at the 16th International Conference in Advertising (ICORIA) which was held in Ghent (Belgium) in June 2017. The conference gathered more than 160 participants from over 30 countries all over the world. Contents Going Beyond: Persuading the Consumer with New Advertising Formats Getting Inside the Game: Effectiveness of In-Game Advertising How to Create Your Ad: An Insight into the Effects of Advertising Execution Styles Doing Good: Corporate Social Responsibility and Consumer Protection Let them Talk: How to Increase and Evaluate Word of Mouth It's All about Context: Situational Influences on Advertising Effects Target Groups Researchers, instructors, and students in the fields of advertising, communication, marketing and media management, as well as practitioners in these areas. The Editors Verolien Cauberghe is Associate Professor of Marketing Communication at Ghent University, Belgium. Liselot Hudders is Assistant Professor of Marketing Communication and Consumer Behavior at Ghent University, Belgium. Martin Eisend is Professor of Marketing at the European University Viadrina, Frankfurt (Oder), Germany.